PRE-OPERATIVE PATIENT PREPARATION IN THE PREVENTION OF SURGICAL SITE INFECTIONS - McBride, Tara; Beamer, Jennifer (Operating Room Nurses Association of Canada Journal, 2007)
In 1999 the Ontario Ministry of Health and Long Term Care granted funding to St. Mary’s General Hospital for a Regional Cardiac Care Center. In July 2003 the cardiac surgery program opened. During the program-planning phase, protocols and procedures related to patient preparation for cardiac surgery were developed. OBJECTIVE: To share policies, protocols and patient teaching tools developed from research driven, evidenced based standards of practice. To complete a one-year review (January to December 2004) and assess the compliance rates with pre-operative patient preparation procedures on all Coronary Artery Bypass Graft (CABG) cardiac surgery patients. DESIGN: Retrospective chart review. SETTING: 191 bed community-based Regional Cardiac Care Centre. PARTICIPANTS: All adult patients undergoing Coronary Artery Bypass Graft (CABG) surgery from January 1st 2004 to December 31st 2004. ANALYSIS: Compliance rate following patient education related to pre-operative washes, assessing completion of pre-operative washes, and location of clipping relative to the Cardiovascular Operating Room (CVOR). CONCLUSION: A team of Registered Nurses was able to effectively implement policies and protocols within a cardiac surgery program that meet the recommended standards of care of the Centers for Disease Control and Prevention (CDC), Operating Room Nurses Association of Canada (ORNAC) and Safer Health Care Now! Initiative. A retrospective chart review has demonstrated that staff consistently apply and document care in accordance with the developed pre-operative wash and hair clipping protocols.